ESTIMATION OF RELATIVE CHLOROPHYLL CONCENTRATIONS IN POTATO (Solanum tuberosum L.) LEAFLET USING VEGETATION REFLECTANCE TECHNIQUES - Loayza, Hildo (2023)
The amount of solar energy absorbed by plants is largely a function of the foliar concentration of photosynthetic pigments. Consequently, low concentrations of chlorophyll can directly limit the photosynthetic potential and thus the primary production of plants. This study describes a non[1]destructive method aiming to estimate the chlorophyll concentrations on potato leaves from the cultivars SA–2563, Pumamaqui and Purranca. This method is based on the interaction between light and vegetation and uses the first derivative of spectral reflectance from the crop canopy. For reference, we used the SPAD units obtained with a previously validated SPAD–502 chlorophyll meter. We found correlations greater than 90% between the amplitudes of signals obtained by deriving the spectral reflectance of leaves at wavelength about 720 nm and the chlorophyll concentrations obtained by the SPAD–502. Overall, this study showed the potential of techniques based on vegetation reflectance as robust indicators for estimating plant biochemical–physiological parameters.